Premature deaths caused by smoking in Sichuan, Southwest China, 2015–2030 - Zhuo Wang (Nature Portfolio, 2021)
Abstract Smoking has a substantial impact on deaths from non-communicable chronic diseases (NCDs). Quantitatively measuring the impact of tobacco control on population health is of great theoretical and practical importance, for governments to make health policy decisions. Focusing on premature deaths, we predicted the deaths by 2030 from major NCDs caused by smoking among people aged 30–69 years in Sichuan Province, Southwest China. We extracted data for 1990–2015 from the Global Burden of Disease Study 2015 and calculated the population attributable fraction, to estimate the proportion of deaths caused by smoking. Four different tobacco control standards were used to estimate 2030 projections for the prevalence of smoking and premature mortality. If smoking prevalence were reduced by 30% from 2015 levels, premature mortality could be expected to decline by 24.4% in 2030, achieving 81.3% of the World Health Organization target for reducing premature mortality by 30%. Compared with the continuation of historical trends, the strongest tobacco control policy scenario would reduce premature mortality by 6.6%, prevent 23,600 deaths, reduce mortality by 7.8%, and increase life expectancy at birth by 0.3 years. Smoking bans represent an important action toward achieving national health goals.